ChemInform Abstract: N‐Methylimidazolium Perchlorate as a New Ionic Liquid for the Synthesis of Bis(pyrazol‐5‐ol)s under Solvent‐Free Conditions. Issue 22 (12th May 2016) - Khaligh, Nader Ghaffari; Hamid, Sharifah Bee Abd; Titinchi, Salam J. J.
Abstract: The method is simple, environmentally benign, and starts from inexpensive substrates.